The scent of attraction and the smell of success: crossmodal influences on person perception - Spence, C (Springer Nature, 2021)
In recent decades, there has been an explosion of research into the crossmodal influence of olfactory cues on multisensory person perception. Numerous peer-reviewed studies have documented that a variety of olfactory stimuli, from ambient malodours through to fine fragrances, and even a range of chemosensory body odours can influence everything from a perceiver’s judgments of another person’s attractiveness, age, affect, health/disease status, and even elements of their personality. The crossmodal and multisensory contributions to such effects are reviewed and the limitations/peculiarities of the research that have been published to date are highlighted. At the same time, however, it is important to note that the presence of scent (and/or the absence of malodour) can also influence people’s (i.e., a perceiver’s) self-confidence which may, in turn, affect how attractive they appear to others. Several potential cognitive mechanisms have been put forward to try and explain such crossmodal/multisensory influences, and some of the neural substrates underpinning these effects have now been characterized. At the end of this narrative review, a number of the potential (and actual) applications for, and implications of, such crossmodal/multisensory phenomena involving olfaction are outlined briefly.